Readability test for basic mathematics textbook integrated challenge based on blended learning to develop skills in the industrial revolution era - Ardiansyah, Adi Satrio; Ferianto, Andika Nur; Dinasari, Arum (Department of Mathematics, Universitas Negeri Semarang, 2021)
The development of technology and information requires education providers to keep up with the times. One of them is the implementation of blended learning which is the challenge for universities. This condition requires lecturers to make learning innovations for the continuity of learning and to achieve learning outcomes. To answer these problems, a Basic Mathematics Textbook will be developed which is integrated with the Challenge Based on Blended Learning (CB-BL) model. This study aims to assess the readability test of the Basic Mathematics Textbook integrated with the CB-BL. Development research was carried out to develop textbook products using the 4D model where one of the stages is Develop through the readability test. The results showed that the Basic Mathematics Textbook integrated with the CB-BL model met the readability test with a score of 94 (Very Good criteria). The readability test results show that the Basic Mathematics Textbook integrated with the CB-BL model can be implemented in the classroom to develop student skills.